(untitled) (Texas Journal of Medical Science, 2024)
The article is devoted to the study of the actual nutrition of 1-4 graders living in rural areas. The number of micronutrients in the daily food of the respondents was determined and compared with the relevant standards. According to the obtained results, it was found that the amount of some vitamins in the daily diet of the subjects is much less than the norm. In the work, necessary recommendations are also given to eliminate the lack of micronutrients and its prevention.